Workup and Management of Persistent Neuralgia following Nerve Block. (19th January 2016) - Weyker, Paul David; Webb, Christopher Allen-John; Pham, Thoha M.
Abstract : Neurological injuries following peripheral nerve blocks are a relatively rare yet potentially devastating complication depending on the type of lesion, affected extremity, and duration of symptoms. Medical management continues to be the treatment modality of choice with multimodal nonopioid analgesics as the cornerstone of this therapy. We report the case of a 28-year-old man who developed a clinical common peroneal and lateral sural cutaneous neuropathy following an uncomplicated popliteal sciatic nerve block. Workup with electrodiagnostic studies and magnetic resonance neurography revealed injury to both the femoral and sciatic nerves. Diagnostic studies and potential mechanisms for nerve injury are discussed.